Penerapan Penyelesaian Diversi di Kepolisian Sektor yang Tidak Memiliki Unit Pelayanan Perempuan dan Anak - Rakha Arfitama Putra; Rena Yulia; Muhamad Romdoni (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
The implementation of diversion for children in conflict with the law constitutes a fundamental component of the juvenile criminal justice system in Indonesia, particularly as an effort to prioritize restorative justice and the protection of children’s rights. In practice, however, diversion at the Sector Police level faces structural challenges, especially in police units that do not have a Women and Children Protection Unit. The handling of diversion cases at the Taman Sari Sector Police illustrates this condition, where diversion is conducted without institutional coordination with the Protection Unit at the District Police level and instead involves external companion institutions. Qualitative juridical-normative analysis supported by interviews reveals that although diversion procedures are formally carried out, their implementation tends to emphasize procedural completion rather than substantive recovery for victims. Case settlements that result solely in apologies, without compensation or other restorative measures, demonstrate insufficient fulfillment of victims’ physical and psychological recovery. This practice reflects a structural gap between normative regulations and institutional capacity at the Sector Police level. The findings indicate that the absence of specialized child investigators and clear coordination mechanisms weakens the quality of legal protection for both child offenders and victims. Strengthening institutional arrangements through the establishment of Protection Units at the Sector Police level or the assignment of trained child investigators, along with clearer regulatory guidance on victim compensation in diversion, is essential to ensure proportional recovery and the realization of restorative justice principles.